Integrating the temulawak approach and R software to optimize students’ mathematical representation - Wulandari, Andhika Ayu; Farahsanti, Isna; Astutiningtyas, Erika Laras; Exacta, Annisa Prima (Universitas Islam Negeri Raden Intan Lampung, 2025)
Representational ability is an important element in understanding mathematical concepts. The temulawak approach (Techniques for Information Discovery, Processing and Insights for Computing), rooted in cybernetic theory, is integrated with R and developed as a learning tool to improve students' mathematical representation skills in understanding probability distribution concepts. The purpose of this study is to determine how integrating the temulawak approach with R software improves students' mathematical representation skills. The experiment was conducted on 18 student subjects enrolled in the Theoretical Descriptive Statistics course for the 2024/2025 academic year. Evaluations were conducted at the beginning of the course and at the end of each learning phase. The results of the analysis using a paired-samples t-test with α = 5% showed an increase in mathematical representation skills from the pretest to the posttest of 44,55%. The effect of this learning is considered significant (d > 0.8). These findings indicate that integrating temulawak and computational technology through R software improves students' mathematical representation skills. This study implies that integrating the temulawak approach with R software can significantly strengthen students' mathematical representation skills and conceptual understanding of probability distributions, thereby confirming the benefits of cybernetic-based learning approaches supported by computational technology.